DISPARITIES IN STUNTING PREVENTION KNOWLEDGE AND PRACTICES AMONG PREGNANT WOMEN IN 3T OUTERMOST ISLANDS VERSUS URBAN AREAS OF RIAU ISLANDS PROVINCE, INDONESIA: A COMPARATIVE CROSS-SECTIONAL STUDY - Risqi Utami; Angga Putri; Prasida Yunita (Pena Cendekia Insani, 2026)
Stunting remains a major public health challenge in Indonesia despite declining prevalence, with disparities in maternal knowledge and preventive practices persisting in outermost, frontier, and least-developed (3T) regions. To compare stunting-prevention knowledge and practices among pregnant women in the 3T outermost islands and a non-3T urban area of the Riau Islands Province, and identify factors associated with adequate knowledge. A comparative cross-sectional study was conducted among 420 pregnant women using multistage cluster sampling. Data were collected using a validated questionnaire and analyzed with chi-square tests and multivariable logistic regression. Women in the 3T islands had lower adequate knowledge (37.6% vs. 63.8%), attendance of 6 ANC contacts (40.5% vs. 77.6%), adherence to 90 iron–folic acid tablets (33.8% vs. 60.5%), and adequate dietary diversity (30.0% vs. 54.8%) (all p < 0.001). Residence in the 3T region (aOR 0.42), tertiary education (aOR 2.98), distance > 5 km to a health facility (aOR 0.55), and nutrition counselling (aOR 2.41) were independently associated with adequate knowledge. Geographic disparities persist, high lighting the need for targeted maternal education, nutrition counselling, and improved access to maternal health services in 3T settings.